Cybersecurity Challenges on the Internet of Things (IoT) - Deepak Nanuru Yagamurthy (North American Journal of Engineering Research, 2021)
The rapid proliferation of the Internet of Things (IoT) has revolutionized industries by enabling unprecedented connectivity and automation through interconnected devices. However, this growth has also introduced significant cybersecurity challenges due to the inherent vulnerabilities of IoT devices. This paper examines the major cybersecurity risks associated with IoT, such as weak authentication, data privacy concerns, and the lack of standardized security protocols. By analyzing current threats, vulnerabilities, and industry practices, we explore potential solutions to mitigate these risks. The paper further discusses emerging technologies like Artificial Intelligence (AI), Machine Learning (ML), and blockchain, which show promise in enhancing IoT security. Additionally, the importance of regulatory frameworks and global standards in shaping the future of IoT cybersecurity is highlighted. The findings underscore the urgent need for robust, scalable, and adaptive security measures to protect the expanding IoT ecosystem from evolving cyber threats.